2010
DOI: 10.2754/avb201079010013
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Effect of Leptin in the Quail Chorioallantoic Membrane

Abstract: Leptin, the product of ob gene, beside its key role in the control of body weight and food consumption, can be involved in the control of embryonic development. Leptin administration in ovo accelerated the embryonic and post-embryonic development in Japanese quail. Although the mechanisms of leptin effects on growth and development acceleration are not clear, stimulation of angiogenesis represents one of plausible explanations. Therefore, the aim of the present study was to investigate the pro-angiogenic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…But no reports have yielded conclusion results. Reports have also suggested that this dual function of leptin depends on multiple factors such as dose, time of incubation, mode of administration and to certain extent the type of species [ 3 , 4 , 8 10 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…But no reports have yielded conclusion results. Reports have also suggested that this dual function of leptin depends on multiple factors such as dose, time of incubation, mode of administration and to certain extent the type of species [ 3 , 4 , 8 10 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For PDT preclinical studies, the chick CAM has been used as an in vivo model, in which photosensitizers were administered mainly intravenously or topically [5,17,20,21]. Along the wellestablished chick CAM model, the CAM of Japanese quail (Coturnix japonica) has also been used in drug testing [22][23][24]. Results obtained in both chicken and quail CAM assays are very similar, but there are some advantages in the use of the quail CAM model [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…These two processes have been analyzed for fractal geometry in our study, using fractal dimension as a statistical descriptor of the space‐filling pattern and density [Parsons‐Wingerter et al, 2000]. This parameter has been used to monitor the action of molecules that increase or inhibit vascular development [Parsons‐Wingerter et al, 2006; Výboh et al, 2010]. Here, the fractal dimension of the YSM vascular network was the parameter used to show that 1 mT and 60 Hz MF inhibited the vascular process when quail eggs were exposed for 6–9 h/day for an incubation period between 48 and 72 h. The inhibition of vascular development is related to lower fractal dimension values, exhibited by Groups 2 and 3 (Table 2).…”
Section: Discussionmentioning
confidence: 99%